Local Expenditure Financing Response in Regencies and Municipalities in Indonesia (Analysis of the Flypaper Effect Phenomenon) - Septianingrum, Nabila Ardyamita; Halim, Abdul; Utami, Tiyas Puji (Journal of Accounting and Investment, 2025)
Research aims: This research aims to analyze the flypaper effect occurrence on regencies and municipalities in Indonesia considering medium-term expenditure framework and their economic conditions.Design/Methodology/Approach: Quantitative methodology with secondary data from 226 regencies/municipalities in Indonesia was used. The first hypothesis testing was to find whether there was different expenditure mean value and if there was any, hypothesis testing about flypaper occurrence would be performed.Research findings: The results show (1) there was no different capital expenditure mean value because there was a target of capital expenditure set for every local government, therefore flypaper effect occurrence hypothesis testing was not performed and (2) there was different operational expenditure mean value and flypaper effect did not occur in rich local governments, but poor ones.Theoretical contribution/ Originality: This research fills the research gap of flypaper effect occurrence on capital expenditure and operational expenditure based on local governments’ economic conditions. Practitioner/Policy implication: This research implies that intergovernmental transfers should be used accordingly and local governments should increase their local own-source revenue so that they wouldn’t be dependent to the transfers from central government.Research limitation/Implication: The limitations of this study are related to data period (abnormal condition of Covid-19) and statistical data (needed further explanation from primary data).Keywords: Flypaper Effect; Economic Conditions; Local Own-Source Revenue; Local Expenditure; Intergovernmental Transfers